Alexander the Great and Julius Caesar: Narratives of Kingship in Several Manuscripts of the Chronique dite de Baudouin d'Avesnes. Issue 1 (2nd January 2019) - Koroleva, Elena
ABSTRACT: This paper discusses the relationship between text and iconography in the manuscripts of the Chronique dite de Baudouin d'Avesnes, a French universal chronicle that was written for a noble lay readership between 1278 and 1281 and circulated widely between the end of the thirteenth and the end of the fifteenth century. The study is specifically focused on the lives of two heroes of Antiquity, Alexander the Great and Julius Caesar. It examines whether both figures, seen as somewhat problematic due to the details of their respective biographies, are depicted as perfect rulers and if that's the case, what means are used to convey this vision.